2022
DOI: 10.3390/ijms23169404
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Platinum Nanoparticles with Biomedical Applications

Abstract: Functionalized platinum nanoparticles have been of considerable interest in recent research due to their properties and applications, among which they stand out as therapeutic agents. The functionalization of the surfaces of nanoparticles can overcome the limits of medicine by increasing selectivity and thereby reducing the side effects of conventional drugs. With the constant development of nanotechnology in the biomedical field, functionalized platinum nanoparticles have been used to diagnose and treat disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…PDA, as the main material of this nanocomposite, is a good free radical scavenger because of its rich phenolic groups, which eliminates the ROS produced in inflammatory reactions [ 21 ]. Pt has a high catalase catalytic activity and can thus catalyze hydrogen peroxide and produce oxygen gas, which significantly improves the hypoxia microenvironment of LN and alleviate LN to a certain extent [ 35 ]. To intuitively confirm the change in oxygen level in the kidney area, we carried out a blood oxygen graph of mouse photoacoustic tomography.…”
Section: Resultsmentioning
confidence: 99%
“…PDA, as the main material of this nanocomposite, is a good free radical scavenger because of its rich phenolic groups, which eliminates the ROS produced in inflammatory reactions [ 21 ]. Pt has a high catalase catalytic activity and can thus catalyze hydrogen peroxide and produce oxygen gas, which significantly improves the hypoxia microenvironment of LN and alleviate LN to a certain extent [ 35 ]. To intuitively confirm the change in oxygen level in the kidney area, we carried out a blood oxygen graph of mouse photoacoustic tomography.…”
Section: Resultsmentioning
confidence: 99%
“…A specific molecule’s conjugation with the surface of nanoparticles can improve penetration into cells by increasing their bioavailability. The functionalization of PtNPs by various molecules possessing a therapeutic effect opens up new possibilities for nanomedicine [ 214 ]. Thus, biosynthesized platinum nanoparticles represent a promising, economical drug for the disease treatment of various etiologies and improving the quality of people’s lives, requiring further study on their physicochemical and biological properties.…”
Section: Discussionmentioning
confidence: 99%
“…Also, studies showed that the presence of platinum nanoparticles when cell cultures were irradiated could result in strongly enhanced breaks in DNA, especially DSBs, mediated by water radicals which may originate from the inner-shell excitation of platinum atoms [50,113,114]. In other studies, Gutiérrez et al [115] discussed the enhanced effect of radiation on cervicaluterine cancer cells (HeLa) when the cancer cells were treated with PEGylated PtNPs functionalized with a fluorescent marker in combination with γ-rays. Results showed that as the radiation dose increased, the number of survived cells decreased in the presence of the nanoparticles.…”
Section: Platinum-based Nanoparticlesmentioning
confidence: 99%